Models of mycorrhizal colonization patterns and strategies induced by biostimulator treatments in Zea mays roots - Pop-Moldovan, Victoria; Corcoz, Larisa; Stoian, Valentina; Moldovan, Cristina; Pleșa, Anca; Vâtcă, Sorin; Stoian, Vlad; Vidican, Roxana (Frontiers in Plant Science, 2022)
Agronomic inputs and technologies, especially fertilizers act on the evolution of the symbiotic partnership between arbuscular mycorrhizal fungi and cultivated plants. The use of the MycoPatt method for the assessment of mycorrhizas in maize roots leads to the extraction of large parameter databases, with an increased resolution over the colonization mechanism. The application of a biostimulator treatment on plants acted toward a reduction of root permissiveness for mycorrhizas. The phenomenon was noticed by an increased colonization variability overlapped on plant nutritional needs. The annual character of the plant was highlighted by the simultaneous presence of arbuscules and vesicles, with a high share of arbuscules in the advanced phenophases. Colonized root parts presented numerous arbuscules dominated areas, in all phenophases, which indicated a continuous formation of these structures and an intense nutrient transfer between partners. Mycorrhizal maps showed the slowing effect of the biostimulator on colonization, with one phenophase delay in the case of biostimulated plants compared to the ones without biostimulator. The forecast models presented gradual colonization in plants without biostimulator, with the expansion of new hyphal networks. The use of biostimulator on plants exhibited a lower permissiveness for new colonization areas and the mechanism was relying on hyphae developed in the former phenophases.